Use of antifibrinolytic therapy in the perioperative period in children - Faryna , Liubov; Biliaiev , Andriy (The Ukrainian Scientific Medical Youth Journal, 2023)
The course of surgical interventions in children can be complicated by the development of perioperative bleeding. The use of drugs with antifibrinolytic action reduces and prevents the development of intraoperative blood loss in adults and children. Antifibrinolytic drugs such as tranexamic acid have been shown to be effective in reducing perioperative blood loss, transfusion in adult patients and children in trauma, cardiosurgical and major orthopedic interventions. However, the use of this drug in the category of high-risk patients and in loading doses > 100 mg/kg may be associated with the development of thromboembolic and convulsive complications. One of the advantages of using aminocaproic acid is wide availability, cost and, at the same time, effectiveness. Comparing the effectiveness of lysine derivatives in patients with craniosynostosis, A.Borst and C. Bonfield note that when using aminocaproic acid compared to tranexamic acid, the level of intraoperative blood loss increases (21 ± 13 vs. 17 ± 10), but it is not statistically significant. Aprotinin, as a drug for reducing blood circulation in cardiosurgical diseases in comparison with lysine derivatives, is more effective for reducing perioperative blood. After The Blood Conservation Using Antifibrinolytics in a Randomized Trial (BART) (Fergusson D. et al. 2008) aprotinin is limited in many countries because of the high rate of thromboembolic complications and increased mortality. Currently, the anti-inflammatory properties of not only aprotinin, but also tranexamic and aminocaproic acids are being actively investigated.